THE DIAGNOTIC VALUE OF COMPUTED TOMOGRAPHY OF 49 HOLLOW VISCUS INJURY PATIENTS DUE TO BLUNT ABDOMINAL TRAUMA - Mai Duc Hung; Nguyen Thi Ly; Ly Lap; Le Van Phuoc (Tạp chí Y học Quân sự, 2023)
Purpose: We aimed to to determine the value of abdominal CT scans in the diagnosis of blunt abdominal trauma with hollow viscus and mesenteric injury. Methods: Retrospective, cross - sectional description. Result: Patients averaged 41.14 ± 14.77 years old; male/female sex ratio ≈ 4.5/1, and the main cause of injuries was traffic accidents (83.7%), with lesions of the small intestine (57.1%), colon (26.5%) and rectum (2.0%). Computed tomography had high specificity in diagnosing the lesion sites, around 1 in cases of the duodenum, small intestine, colon, and rectum. Value of computed tomography with general hollow visceral lesions: the sensitivity was 61.9% and the specificity was 86.0%. Signs of hollow visceral injury with high specificity were free air in the abdomen, free fluid in the abdomen, extravasation of the contrast medium, gas in the gastrointestinal wall, and gastrointestinal wall discontinuity with specificity equal to 100%. The sensitivity of the signs: abdominal free air and gastrointestinal wall thickness were 71.0%.